Marked improvement of breathing status by surgical mandibular advancement in a patient with Treacher-Collins syndrome. Issue 6 (November 2020) - Ogisawa, Shouhei; Sawatani, Yuta; Shimura, Michiko; Himejima, Akio; Tonogi, Morio; Kawamata, Hitoshi
Abstract: Treacher-Collins syndrome (TCS) is an autosomal dominant disease. TCS newborns have high mortality due to upper airway obstruction. Here, we reported a successful surgical approach in an adult patient with TCS who showed severe sleep apnea. The patient was a 32-year-old female who was diagnosed with obstructive sleep apnea (apnea hypopnea index: 116.1 /hr, apnea index: 75.2 /hr, hypopnea index: 40.8 /hr). Cephalometric analysis showed poor mandibular development (SNA: 80°, SNB: 67°, ANB: 11°) and deformity of nostril. We conducted surgical mandibular advancement, functional genioplasty, and expansion of the piriform aperture. Cephalometric analysis after surgery found improved skeletal morphology (SNA: 80°, SNB: 73°, ANB: 7°). Comparison of three-dimensional imaging before and after surgery showed that the airway had expanded. Polysomnography after surgery showed improvement to normal values (apnea hypopnea index : 2.7 /hr, apnea index: 0.8 /hr, hypopnea index: 1.9 /hr). Surgical mandibular advancement and functional genioplasty expanded the airway, and shaving of the piriform aperture corrected nasal respiratory disorder. Then, these surgical procedures improved severe sleep apnea in this patient.